Influence of job satisfaction and management information systems on employee performance at PT. Pawnshop in Palopo City - Faradhila Maskur; Adil Basir; Sari Ratna Dewi (Global Academy of Multidisciplinary Studies, 2024)
Purpose: This study aimed to analyze the effect of job satisfaction and management information systems on employee performance at PT. Pawnshops in Palopo City. Research methodology: This study applied a quantitative approach with a total sampling technique, involving 38 employees as respondents. Primary data were collected through structured questionnaires and analyzed using SPSS version 23, employing descriptive statistics and multiple regression analysis to test the hypotheses. Results: The findings indicate that both job satisfaction and management information systems have positive and significant effects on employee performance. The coefficient of determination (R²) is 0.539, showing that 53.9% of the variation in employee performance can be explained by the two independent variables, while the remaining 46.1% is influenced by other factors outside this study. Conclusions: This study confirms that higher levels of job satisfaction and effective use of management information systems contribute significantly to enhancing employee performance at PT. Pawnshops in Palopo City: Limitations: This study was limited by the relatively small sample size and restricted to one branch of PT. Pawnshops and may not fully represent other branches or regions. Contribution: This study contributes to the fields of human resource management and information systems by providing empirical evidence of the joint role of job satisfaction and information systems in improving organizational performance. These findings can serve as a reference for managers of similar institutions to optimize employee outcomes.